Hepatitis B virus exposure and vaccination in a cohort of people who inject drugs: What has been the impact of targeted free vaccination?. Issue 2 (22nd January 2013) - Winter, Rebecca J; Dietze, Paul M; Gouillou, Maelenn; Hellard, Margaret E; Robinson, Priscilla; Aitken, Campbell K
Abstract Background and Aim Forty percent of new hepatitis B virus (HBV) infections in Australia occur in people who inject drugs (PWID); long‐term infection carries the risk of serious liver disease. HBV incidence among Australian PWID has not been measured since the advent of targeted (2001) and adolescent school‐based "catch‐up" (1998) vaccination programs. We measured HBV incidence and prevalence in a cohort of PWID in Melbourne, Australia and examined demographic and behavioral correlates of exposure and vaccination. Methods Community‐recruited PWID were surveyed about blood‐borne virus risk behaviors and their sera tested for HBV markers approximately three‐monthly over three years. Incidence was assessed using prospectively collected data. A cross‐sectional design was used to examine prevalence of HBV exposure and vaccination at baseline. Poisson regression was used to identify correlates of HBV exposure and vaccination. Results At baseline, 33.1% of participants (114/344) had been vaccinated against HBV, 40.4% (139/344) had been exposed (previously or currently infected), and 26.5% (91/344) were susceptible. HBV incidence was 15.7 per 100 person‐years. Independent associations with HBV exposure included female gender, South‐East Asian ethnicity, drug treatment in the past three months, injecting in prison, and prior exposure to hepatitis C virus. Independent associations with vaccination included being ≤ 25 years old, reporting HBV vaccination, and never having been to prison. Conclusions HBV infection continues at high incidence among Australian PWID despite the introduction of free vaccination programs. Innovative methods are needed to encourage PWID to complete HBV vaccination.